Pengaruh Brand Positioning Terhadap Keputusan Penggunaan Aplikasi Fintech Lending Kredivo - Indra Adrianto; Intan Miraka Lailya; Eman Sulaeman (Peneliti.net, 2023)
Fintech lending in Indonesia has developed very advanced, this is due to the ease of use and effectiveness in terms of finance that makes Indonesian people interested. One of the Fintech lending, namely kredivo, Kredivo is a P2PL application which provides the first fast credit loan solution in Southeast Asia that allows consumers to shop online with credit directly without the need to use a credit card. The implementation of Brand Positioning in this study was measured from the respondents' knowledge of Attributes, Benefits and Beliefs and Values. Respondents were also asked about their perceptions about the decision to use Kredivo. The results of this study indicate that brand positioning has an effect on the decision to use kredivo. This can be seen from the high level of correlation and also the results that show the relationship between Brand Positioning and the decision to use is in a strong relationship